GAMERS' MOTIVATION FOR MAKING MICROTRANSACTIONS IN THE GAMES THEY PLAY: A CASE STUDY OF THE SMALL DISCORD WAR THUNDER COMMUNITY IN INDONESIA - Habi Burahman El Sirazi Situmeang; Ezra Aufa Razqa; Dimas Adji Maulana; Doni Andrian; Ikhah Malikhah (Yayasan Multidimensi Kreatif, 2025)
This study aims to determine the motivations of War Thunder players to engage in microtransactions in the game. Game progress can be achieved without any microtransactions, but they are time-consuming. This study aims to determine the factors that motivate players to engage in microtransactions in War Thunder. The research method used was a descriptive qualitative case study approach, while the sampling technique was purposive sampling. Data were collected through interviews with War Thunder players who are members of the Discord community. We selected ten individuals to conduct interviews, and they engaged in microtransactions to accelerate their game progress. The results showed that the primary motivations for players to engage in microtransactions were to accelerate game progress (grinding) and gain a comfortable playing experience, particularly through the Premium Account and Premium Vehicle features. Discounts, particularly substantial discounts on premium vehicle packages, were the dominant drivers in purchasing decisions. This study also found that microtransactions were not undertaken to gain social status or dominance over time, but rather driven by personal needs and time efficiency. From a motivational theory perspective, this behavior aligns with McClelland's Theory of Needs, particularly the need for achievement and self-satisfaction. Thus, microtransactions in War Thunder are understood as a means of supporting the gaming experience, not as a tool for social competition.